Death Anxiety Level among Patients with Chronic Renal Failure Undergoing Hemodialysis - Anneke Dewina; Etika Emaliyawati; Atlastika Praptiwi (Journal of Nursing Care, 2018)
Chronic renal failure (CRF) is one of chronic diseases that can decrease the quality of life and trigger anxiety that is formed by negative thinking, including thought of death. The excessive thought of death will cause stress. This situation will have an impact on care planning, preparation for facing death and difficulties in achieving a dignified quality of death. This study aimed to identify the level of death anxiety among CRF patients undergoing haemodialysis. This study used a quantitative descriptive method involving 73 patients recruited by using a consecutive sampling technique. Data were collected by using a Death Anxiety Scale (DAS) Templer instrument that was adapted for haemodialysis patient. Data were analyzed using descriptive statistics (mean, frequency, and percentage).The results of this study showed that nearly half of the patients had moderate death anxiety (n=35), 27.4% respondents (n=20) experienced low death anxiety, and 24.7% respondents (n=18) experienced high death anxiety. Based on the results, it is necessary to manage the death anxiety of CRF patients undergoing haemodialysis. Some potential approaches may include spiritual therapy, group counselling during haemodialysis, cognitive therapy (positive perception strengthening), and health education related to haemodialysis procedures and chronic renal failure.Keyword : Chronic renal failure, death anxiety, haemodialysis. Tingkat Kecemasan Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisis dalam Menghadapi KematianAbstrakPenyakit gagal ginjal kronik dapat menurunkan kualitas hidup sehingga memicu kecemasan akibat dari pemikiran negatif termasuk pemikiran akan kematian. Pemikiran kematian yang berlebihan menimbulkan stres tersendiri sehingga berdampak pada perencanaan perawatan, persiapan menghadapi kematian dan sulitnya mencapai kualitas kematian yang bermartabat. Penelitian ini bertujuan untuk mengetahui tingkat kecemasan pasien gagal ginjal kronik yang menjalani hemodialisis dalam menghadapi kematian. Penelitian deskriptif kuantitatif ini melibatkan 73 pasien gagal ginjal kronik yang menjalani hemodialisis diambil dengan teknik consecutive sampling. Pengumpulan data menggunakan instrumen Death Anxiety Scale (DAS) Templer yang diadaptasi untuk pasien hemodialisis. Data dianalisis dengan statistik deskriptif (frekuensi dan persentasi). Hasil penelitian menunjukkan separuh dari jumlah pasien gagal ginjal kronik yang menjalani hemodialisis mengalami kecemasan kematian tingkat sedang (n=35), 27.4% responden (n=20) mengalami kecemasan rendah, dan 24.7% responden (n=18) mengalami kecemasan kematian tinggi. Berdasarkan hasil tersebut perlu dilakukan pengelolaan terhadap kecemasan menghadapi kematian pasien gagal ginjal kronik yang menjalani hemodialisis. Bentuk pengelolaan kecemasan menghadapi kematian diantaranya dengan terapi spiritualitas, konseling kelompok, terapi kognitif (penguatan persepsi positif), dan pemberian pendidikan kesehatan terkait dengan prosedur hemodialisis dan penyakit gagal ginjal kronik.Kata kunci : Gagal ginjal kronik, hemodialisis, kecemasan menghadapi kematian.